Signaling through timing of stock splits - Iannino, Maria Chiara; Zhang, Min; Zhuk, Sergey (Journal of Corporate Finance, 2024)
We develop a dynamic structural model of stock splits, in which managers signal their private information through the timing of the split decisions. Our approach is consistent with the empirical evidence which shows that the majority of stock splits have a 2:1 ratio of old-to-new shares, but are announced at various pre-split price levels. Moreover, it explains why split announcement returns are decreasing with the pre-split price. In addition, by matching the model to the data, we estimate the nominal share price preferences of investors and decompose the split announcement return into the value of new information and the signalling cost.